Brain Parenchymal Signal Abnormalities Associated with Developmental Venous Anomalies in Children and Young Adults - Linscott, L.L. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: Abnormal signal in the drainage territory of developmental venous anomalies has been well described in adults but has been incompletely investigated in children. This study was performed to evaluate the prevalence of brain parenchymal abnormalities subjacent to developmental venous anomalies in children and young adults, correlating with subject age and developmental venous anomaly morphology and location. MATERIALS AND METHODS: Two hundred eighty-five patients with developmental venous anomalies identified on brain MR imaging with contrast, performed from November 2008 through November 2012, composed the study group. Data were collected for the following explanatory variables: subject demographics, developmental venous anomaly location, morphology, and associated parenchymal abnormalities. Associations between these variables and the presence of parenchymal signal abnormalities (response variable) were then determined. RESULTS: Of the 285 subjects identified, 172 met inclusion criteria, and among these subjects, 193 developmental venous anomalies were identified. Twenty-six (13.5%) of the 193 developmental venous anomalies had associated signal-intensity abnormalities in their drainage territory. After excluding developmental venous anomalies with coexisting cavernous malformations, we obtained an adjusted prevalence of 21/181 (11.6%) for associated signal-intensity abnormalities in developmental venous anomalies. Signal-intensity abnormalities were independently associated with younger subject age, cavernous malformations, parenchymal atrophy, and deep venous drainage of developmental venous anomalies. CONCLUSIONS: Signal-intensity abnormalities detectable by standard clinical MR images were identified in 11.6% of consecutively identified developmental venous anomalies. Signal abnormalities are more common in developmental venous anomalies with deep venous drainage, associated cavernous malformation and parenchymal atrophy, and younger subject age. The pathophysiology of these signal-intensity abnormalities remains unclear but may represent effects of delayed myelination and/or alterations in venous flow within the developmental venous anomaly drainage territory.